Comparative Analysis of Financial Performance Before and After the Acquisition of the Acquisiting Company (Case Study of PT. Telkom Indonesia) - Sephita, Indira; Nurazi, Ridwan (Formosa Journal of Multidisciplinary Research, 2024)
Acquisition is a type of business development strategy. Acquisitions affect the financial success of the company. An organization can determine the results of its operational activities through its financial results, which are presented in numerical figures. Key figures can be used to confirm financial results. This study measures and compares the financial performance from 2015-2018 and 2020-2023 before and after the acquisition of PT Telkom Indonesia (Persero) Tbk. Such research uses descriptive and comparative methods as well as quantitative methodology. Secondary data can be obtained from financial accounting (financial annual report). The current ratio and return on investment before and after the acquisition differed significantly according to the analysis and conclusions. There is no noticeable change in the ratio of debt to balance sheet volume and pre-sales to post-transaction sales.